Leiomyoma of the gallbladder: a case report with review of the literature and discussion of the differential diagnosis. Issue 2 (12th February 2010) - Wachter, D L; Büttner, M J; Grimm, K; Hartmann, A; Agaimy, A
Abstract : Mesenchymal neoplasms of the gallbladder are rare, and most represent sarcomas of various histological types. To our knowledge, only a few patients with multiple Epstein–Barr virus (EBV)-associated smooth muscle tumours of the gallbladder in the setting of immunodeficiency have been reported in the English literature, but no single case of conventional leiomyoma has been well documented to date. A case of gallbladder leiomyoma in a healthy 34-year-old woman is described here. The tumour was found incidentally on a routine ultrasound examination and was removed by simple cholecystectomy. The patient is alive and well at last follow-up, 6 months after surgery. Histology and immunohistochemistry were consistent with a benign smooth muscle neoplasm that is very similar to conventional uterine leiomyoma. The tumour was negative for both EBV-encoded nuclear RNAs and EBV latent membrane antigen. The patient had no history of uterine leiomyoma or other neoplasms or clinical evidence of an immune defect. Leiomyoma should be included in the differential diagnosis of spindle cell tumours of the gallbladder and must be distinguished from leiomyosarcoma and the rare gastrointestinal stromal tumour-like neoplasms reported recently at this unusual anatomical site.